A coleção didática Tapete Verde: do projeto à sua produção gráfica (década de 1970 - Rio Grande do Sul) - Ramil, Chris de Azevedo (2013)
This research aimed to examine the collection of textbooks Tapete Verde in its editorial and graphics aspects, identifying the stages of design and graphic production at Editora Globo, and relate the elements of recurrence in graphic design, information design and reading design in relation to pedagogical aspects. The didactic collection Tapete Verde is made of Integrated Books, Activity Books and Teacher Books, in separate volumes from 1st to 4th grade, was published in the 1970s in Rio Grande do Sul by Editora Globo and its authors are the local teachers of Porto Alegre, Nelly and Teresa Cunha Iara Palmini Fabretti. The textbook can be considered an important source of information about the context in which it was produced, and may reveal aspects of society and of the time by analyzing the market that circulated, editorial production, the pedagogical goals of its visuality and materiality, enabling communication beyond the written content, sensitizing the reader to the visual phenomenon and its informative potential. From graphic design to graphic production of a didactic collection, features established in these steps may be responsible for setting guidelines, interfere with the transmission of content and cause different behaviours in readers, both in students and in teachers, using the books in the classroom. With the studies about textbook and graphic design, the data indicate that the investigated collection can add important considerations in the research fields of history textbooks and education in Rio Grande do Sul, as well as to the printing and publishing history of the region. Furthermore, this work aims to strengthen the incentive for researches about the confluence of conceptual references in the fields of education and design, seeking new contributions by both the historical and current perspectives.